The MTHFR C677T Variant is Associated with Responsiveness to Disulfiram Treatment for Cocaine Dependency - Spellicy, Catherine; Kosten, Thomas; Hamon, Sara; Harding, Mark; Nielsen, David A. (Frontiers in Psychiatry, 2013)
Objective: Disulfiram is a one of the few pharmacotherapies for cocaine addiction that shows promise. Since disulfiram and cocaine both affect levels of global methylation we hypothesized the MTHFR gene, whose product is involved in supplying methyl groups for DNA and protein methylation, may be associated with responsiveness to disulfiram in cocaine-dependent individuals. Methods: Sixty-seven cocaine dependent patients were stabilized on methadone for two weeks and then randomized into disulfiram (250 mg/day, N = 32) and placebo groups (N =35) for 10 weeks. Patients were genotyped for the MTHFR (rs1801133, also known as C677T) polymorphism and the data was evaluated for association with cocaine-free urines in the disulfiram or placebo groups. Data from patients that completed all ten weeks of the study (N = 56) were analyzed using repeated measures analysis of variance (ANOVA), corrected for population structure. Results: The CT or TT MTHFR genotype group (N = 32) dropped from 73% to 52% on disulfiram (p = 0.0001), while the placebo group showed no treatment effect. The CC MTHFR genotype group (N = 24) showed a reduced, but still significant, reduction in cocaine-positive urines on disulfiram compared to placebo; 81-69% (p = 0.007). Conclusion: This study indicates that a patient’s MTHFR genotype may be used to identify individuals who might show improved response to disulfiram treatment for cocaine dependence.